MANAGEMENT INTERPROFESSIONAL EDUCATION OF ETHICS COURSE ON HANDLING NONCOMMUNICABLE DISEASES - Rr. Sri Endang Pujiastuti; Sri Widiyati; Sherly Metasari; Titin Suheri; Mugi Hartoyo; Agussalim Agussalim; Ainun Mutmainah (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
Interprofessional education has been defined as a process learning program which includes learning outcomes, lecturers, material topics and skills enabling a synergistic influence of grouped student competence, so that interprofessional education becomes one of the initial stages for introducing collaboration and teamwork to students so that they can be applied of work. The explore the appropriateness and meaningfulness of Ethics and Health Law Course-based learning for nursing students. The research is a research and development design whose stages were carried out for 6 months with a research sample of 40 respondents, namely first semester students of the postgraduate nursing program. The results of this study showed that the significant for the materials of ethics, curriculum, learning outcomes (P=0.000). The students showed active participation, communication and good collaboration regarding health problem solving on handling non-communicable diseases. Management of interprofessional education (pretest = 54.32 and posttest mean 67.48) is needed in health education, as an approach to the learning process, includes the flexibility to respond to the specific (P=0.002), self-identified learning needs of students (P= 0.000). The results of the focus group discussion showed that knowing how to learn, having high expectations in problem solving, applying competencies to case tasks, collaborating with others, and being creative are all signs of a capable practitioner. There are important characteristics that determine the effectiveness of interprofessional education ethics courses, including faculty and students who consider their roles important to the team, open communication, autonomy, and equality of resources so that interprofessional education has a positive impact on the development of holistic care to improve the quality of patient care.